Transparent conductive film

A transparent conductive film with controlled crystallinity and crystal grain size, and a curable resin layer, addresses the durability and definition issues in resistive touch panels, providing both excellent pen sliding and heavy pressure durability.

JP2024180466AActive Publication Date: 2024-12-26TOYOBO CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024177087
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-09-29
Filing Date
2024-10-09
Publication Date
2024-12-26
Estimated Expiration
2041-08-05

AI Technical Summary

Technical Problem

Conventional transparent conductive films used in resistive touch panels suffer from inadequate pen sliding durability and pen heavy pressure durability, leading to issues such as cracking, peeling, and abrasion when used with pens, while also failing to maintain high-definition images.

Method used

A transparent conductive film with a laminated indium-tin composite oxide on a transparent plastic film base material, controlled crystallinity and crystal grain size, and a curable resin layer, ensuring ON resistance of 10kΩ or less, surface resistance increase of 1.5 or less, and transmission image clarity of 250% or more, combined with a thickness of 100 to 250 μm.

Benefits of technology

The film achieves excellent pen sliding and heavy pressure durability, preventing cracking, peeling, and abrasion, while maintaining high-definition images, making it suitable for resistive touch panels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024180466000005
    Figure 2024180466000005
  • Figure 2024180466000006
    Figure 2024180466000006
  • Figure 2024180466000007
    Figure 2024180466000007
Patent Text Reader

Abstract

To provide a transparent conductive film which is excellent in pen slide durability, a pen weight pressurization durability, and high definition, when being used in a touch panel.SOLUTION: There is provided a transparent conductive film, wherein a crystal particle size of a transparent conductive film of an indium-tin complex oxide is 10 to 100 nm, a degree of crystallization of the transparent conductive film of the indium-tin complex oxide is 20 to 80%, the transparent conductive film of the indium-tin complex oxide contains 0.5 to 10 mass% of tin oxide, thickness of the transparent conductive film of the indium-tin complex oxide is 10 to 30 nm, when three-dimensional surface roughness SRa of the transparent conductive film of the indium-tin complex oxide is represented by X, X is 1 to 100 nm, and when three-dimensional surface roughness SRa on a surface opposite to the side of the transparent conductive film on a transparent plastic film base material is represented by Y, (X3+Y3)1 / 3 is 140 nm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent conductive film having a transparent conductive film of crystalline indium-tin composite oxide laminated on a transparent plastic film substrate, and in particular to a transparent conductive film that has excellent pen sliding durability, pen heavy pressure durability, and high definition when used in a resistive touch panel. [Background technology]

[0002] Transparent conductive films, which are made by laminating a transparent, low-resistance thin film onto a transparent plastic substrate, are widely used in electrical and electronic applications that utilize their electrical conductivity, such as in flat panel displays such as liquid crystal displays and electroluminescence (EL) displays, and as transparent electrodes in touch panels.

[0003] Resistive touch panels are a combination of a fixed electrode made of a glass or plastic substrate coated with a transparent conductive thin film and a movable electrode (=film electrode) made of a plastic film coated with a transparent conductive thin film, and are used by overlapping them on the top of a display. The film electrode is pressed with a finger or pen to bring the transparent conductive thin films of the fixed electrode and film electrode into contact with each other, which serves as an input for the touch panel's position recognition. Compared to a finger, a pen often exerts a stronger force on the touch panel. Continuous input with a pen on a touch panel can cause damage such as cracks, peeling, and wear on the transparent conductive thin film on the film electrode side. In addition, if a force stronger than that expected for normal use is applied to the touch panel, such as hitting the touch panel hard with a pen or inputting with a very strong force, the transparent conductive thin film can crack, peel, and be destroyed. To solve these problems, there is a demand for a transparent conductive film that has both excellent pen sliding durability and excellent pen heavy pressure durability. In addition, there is a demand for high-definition images on touch panels.

[0004] As a means for improving the pen sliding durability, there is a method of making the transparent conductive thin film on the film electrode side crystalline (for example, see Patent Document 1). However, conventional transparent conductive films have been realized with excellent pen sliding durability by controlling the crystallinity of indium-tin composite oxide. However, conventional transparent conductive films were insufficient when subjected to the pen heavy pressure durability test described below. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2004-071171 A Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above-mentioned conventional problems, an object of the present invention is to provide a transparent conductive film that has excellent pen sliding durability and heavy pen pressure durability when used in a touch panel, and is capable of providing high-definition images. [Means for solving the problem]

[0007] The present invention has been made in view of the above circumstances, and the transparent conductive film of the present invention, which is able to solve the above problems, has the following configuration. 1. A transparent conductive film having a transparent conductive film of indium-tin composite oxide laminated on one side of a transparent plastic film substrate, wherein the ON resistance of the transparent conductive film of the transparent conductive film in the following pen sliding durability test is 10 kΩ or less, and furthermore, the increase in the surface resistance of the transparent conductive film in the following pen heavy pressure test is 1.5 or less, and furthermore, the sum of the transmitted image clarity of the transparent conductive film at comb widths of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm is 250% or more and less than 500%. (Pen sliding durability test method) The transparent conductive film according to the present invention is used as one panel plate, and a transparent conductive thin film made of an indium-tin composite oxide thin film (tin oxide content: 10% by mass) having a thickness of 20 nm is used as the other panel plate by sputtering on a glass substrate. The two panel plates are arranged with the transparent conductive thin films facing each other via epoxy beads having a diameter of 30 μm, and the panel plate on the film side and the panel plate on the glass side are attached with a double-sided tape having a thickness of 170 μm to prepare a touch panel. Next, a load of 2.5 N is applied to a polyacetal pen (tip shape: 0.8 mmR) and a linear sliding test of 180,000 reciprocations is performed on the touch panel. In this test, the load of the pen is applied to the surface of the transparent conductive film according to the present invention. The sliding distance is 30 mm, and the sliding speed is 180 mm / sec. After this sliding durability test, the ON resistance (resistance value when the movable electrode (film electrode) and fixed electrode come into contact) is measured when the sliding part is pressed with a pen load of 0.8 N. (Pen weight pressure test method) The transparent conductive film according to the present invention cut to 50 mm x 50 mm is used as one panel plate, and a transparent conductive thin film made of an indium-tin composite oxide thin film (tin oxide content: 10 mass%) having a thickness of 20 nm is used as the other panel plate by a sputtering method on a glass substrate. The two panel plates are arranged with the transparent conductive thin film facing each other via epoxy beads having a diameter of 30 μm, and the panel plate on the film side and the panel plate on the glass side are attached with double-sided tape adjusted to a thickness of 120 μm to produce a touch panel. A load of 35 N is applied with a polyacetal pen (tip shape 0.8 mmR) at a position 2.0 mm from the end of the double-sided tape, and linear sliding is performed 10 times (reciprocating 5 times) parallel to the double-sided tape. In this test, the load of the pen is applied to the surface of the transparent conductive film according to the present invention. The sliding distance at this time is 30 mm, and the sliding speed is 20 mm / sec. Sliding is performed at a position where there are no epoxy beads. After sliding, the transparent conductive film is removed and the surface resistance (four-terminal method) is measured at any five points on the sliding area, and the average value is calculated. When measuring the surface resistance, four terminals are arranged in a direction perpendicular to the sliding area, with the sliding area between the second and third terminals. The average surface resistance value of the sliding area is divided by the surface resistance value of the unslided area (measured using the four-terminal method) to calculate the rate of increase in surface resistance value. 2. The crystal grain size of the transparent conductive film of indium-tin composite oxide is 10 to 100 nm, the crystallinity of the transparent conductive film of indium-tin composite oxide is 20 to 80%, the transparent conductive film of indium-tin composite oxide contains 0.5 to 10 mass % of tin oxide, the thickness of the transparent conductive film of indium-tin composite oxide is 10 to 30 nm, and when the three-dimensional surface roughness SRa of the transparent conductive film of indium-tin composite oxide is X, X is 1 to 100 nm, and further when the three-dimensional surface roughness SRa of the surface opposite to the transparent conductive film on the transparent plastic film substrate is Y, (X 3 +Y 3 ) 1 / 3 2. The transparent conductive film according to claim 1, wherein the thickness of the transparent conductive film is 140 nm or less. 3. The transparent conductive film according to claim 1 or 2 above, in which the transparent conductive film does not peel off when an adhesion test (JIS K5600-5-6:1999) is conducted on the surface of the transparent conductive film, and in which a bending resistance test (JIS K5600-5-1:1999) is conducted on the transparent conductive film side of the indium-tin composite oxide of the transparent conductive film, and when the bending portion is observed with a 10x magnifying glass, the mandrel diameter at which cracks or peeling occurs is smaller than 20 mm. 4. The transparent conductive film according to any one of the above items 1 to 3, wherein the transparent conductive film has a thickness of 100 to 250 μm. 5. The transparent conductive film according to any one of the above items 1 to 4, which has a curable resin layer between a transparent conductive film of indium-tin composite oxide and a transparent plastic film substrate. Effect of the Invention

[0008] According to the present invention, it is possible to provide a transparent conductive film that has both excellent pen sliding durability and excellent pen heavy pressure durability and is capable of providing high-definition images. The obtained transparent conductive film is extremely useful for applications such as resistive touch panels. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a schematic diagram showing an example (part 1) of the longest part of a crystal grain in the present invention. [Diagram 2] FIG. 4 is a schematic diagram showing another example (part 2) of the longest part of a crystal grain in the present invention. [Diagram 3] FIG. 4 is a schematic diagram showing another example (part 3) of the longest part of a crystal grain in the present invention. [Figure 4] FIG. 4 is a schematic diagram showing another example (No. 4) of the longest part of a crystal grain in the present invention. [Diagram 5] FIG. 2 is a schematic diagram for explaining the position of a center roll in an example of a sputtering device preferably used in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The transparent conductive film of the present invention is a transparent conductive film having a transparent conductive film of indium-tin composite oxide laminated on one surface of a transparent plastic film substrate, and it is preferable that the ON resistance of the transparent conductive film of the transparent conductive film in the following pen sliding durability test is 10 kΩ or less, and further that the increase rate of the surface resistance value of the transparent conductive film in the following pen heavy pressure test is 1.5 or less, and further that the sum of the transmitted image clarity of the transparent conductive film at comb widths of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm is 250% or more and less than 500%. (Pen sliding durability test) The transparent conductive film according to the present invention was used as one panel plate, and a transparent conductive thin film made of an indium-tin composite oxide thin film (tin oxide content: 10% by mass) having a thickness of 20 nm was used as the other panel plate by sputtering on a glass substrate. The two panel plates were arranged with epoxy beads having a diameter of 30 μm so that the transparent conductive thin films faced each other, and the panel plate on the film side and the panel plate on the glass side were attached with a double-sided tape having a thickness of 170 μm to produce a touch panel. Next, a load of 2.5 N was applied to a polyacetal pen (tip shape: 0.8 mmR), and a linear sliding test of 180,000 reciprocations was performed on the touch panel. In this test, the load of the pen was applied to the transparent conductive film surface according to the present invention. The sliding distance at this time was 30 mm, and the sliding speed was 180 mm / sec. After this sliding durability test, the ON resistance (resistance value when the movable electrode (film electrode) and the fixed electrode contact each other) was measured when the sliding part was pressed with a pen load of 0.8 N. (Pen pressure test) The transparent conductive film according to the present invention was cut to 50 mm x 50 mm and used as one panel plate, and a transparent conductive thin film made of an indium-tin composite oxide thin film (tin oxide content: 10 mass%) having a thickness of 20 nm was used as the other panel plate by sputtering on a glass substrate. The two panel plates were arranged with epoxy beads having a diameter of 30 μm interposed between them so that the transparent conductive thin films faced each other, and the panel plate on the film side and the panel plate on the glass side were attached with double-sided tape adjusted to a thickness of 120 μm to produce a touch panel. A load of 35 N was applied with a polyacetal pen (tip shape 0.8 mmR) at a position 2.0 mm from the end of the double-sided tape, and linear sliding was performed 10 times (reciprocating 5 times) parallel to the double-sided tape. In this test, the load of the pen was applied to the transparent conductive film surface according to the present invention. The sliding distance at this time was 30 mm, and the sliding speed was 20 mm / sec. However, the sliding was performed at a position where there were no epoxy beads. After sliding, the transparent conductive film is removed and the surface resistance (four-terminal method) is measured at any five points on the sliding area, and the average value is calculated. When measuring the surface resistance, four terminals are arranged in a direction perpendicular to the sliding area, with the sliding area between the second and third terminals. The average surface resistance value of the sliding area is divided by the surface resistance value of the unslided area (measured using the four-terminal method) to calculate the rate of increase in surface resistance value.

[0011] The transparent conductive film of the present invention is excellent in pen sliding durability and pen heavy pressure durability. Pen sliding durability and pen heavy pressure durability are contradictory properties. First, the pen sliding durability will be described. In the transparent conductive film of indium-tin composite oxide excellent in pen sliding durability, the transparent conductive film has a high crystallinity and a large crystal grain size. The crystallinity and crystal grain size will be described. The part having a circular or polygonal region observed under a transmission electron microscope is defined as a crystal (= crystal grain) of the transparent conductive film, and the other part is defined as amorphous. A high crystallinity indicates a high proportion of crystals. A large crystal grain size indicates a large circular or polygonal region observed under a transmission electron microscope. A transparent conductive film with a high crystallinity has a high proportion of hard crystals, and a large crystal grain size has a large strain around the crystal grains, so that the transparent conductive film becomes hard and has excellent pen sliding durability. Next, the pen heavy pressure durability will be described. A transparent conductive film of indium-tin composite oxide having excellent pen heavy pressure durability must have a low crystallinity, a small crystal grain size, and a small three-dimensional surface roughness of the transparent conductive film. The three-dimensional surface roughness will be described later. First, a transparent conductive film with a low crystallinity has a high proportion of soft amorphous matter, and a film with a small crystal grain size has a small strain around the crystal grains, so that the transparent conductive film is less likely to crack even when a load is applied, and therefore has excellent pen heavy pressure durability. As described above, it can be seen that pen sliding durability and pen heavy pressure durability are contradictory properties. As a result of the investigation, it was discovered that by controlling the crystallinity and crystal grain size of the transparent conductive film, both pen sliding durability and pen heavy pressure durability can be achieved. A transparent conductive film having a transparent conductive film that achieves both pen sliding durability and pen heavy pressure durability will be described.

[0012] In the present invention, if the ON resistance of the transparent conductive film of the transparent conductive film in the pen sliding durability test is 10 kΩ or less, it is preferable because cracks, peeling, wear, etc. are suppressed in the transparent conductive film even if continuous input is made to the touch panel with a pen. In one embodiment, the ON resistance may be 9.5 kΩ or less, more preferably 5 kΩ or less. For example, the ON resistance may be 3 kΩ or less, 1.5 kΩ or less, and preferably 1 kΩ or less. If the ON resistance is 0 kΩ, the pen sliding durability is very excellent, and in the present invention, the ON resistance can be 0 kΩ. The ON resistance may be, for example, 3 kΩ or more, or 5 kΩ or more. By keeping the ON resistance within this range, cracks, peeling, wear, etc. on the transparent conductive film are suppressed even when continuous input is made to the touch panel with a pen. In one embodiment, these upper and lower limits may be combined as appropriate.

[0013] In the present invention, it is desirable that the rate of increase in the surface resistance of the transparent conductive film in the pen weight pressure test is 1.5 or less. By having such a characteristic, for example, even if a force stronger than that expected in normal use is applied, cracks, peeling, etc. can be suppressed in the transparent conductive film. More preferably, the rate of increase in the surface resistance is 1.2 or less, and particularly preferably 1.0 (no increase). Here, the increase rate of the surface resistance value of the transparent conductive film according to the present invention is preferably 1.0 or more.

[0014] In one embodiment, the ON resistance of the transparent conductive film in a pen sliding durability test is 0.05 kΩ or more and 9.5 kΩ or less, and the increase rate of the surface resistance value of the transparent conductive film in a pen heavy pressure (durability) test is 1.0 or more and 1.5 or less. As described above, pen sliding durability and pen heavy pressure durability are usually contradictory properties. In the present invention, these two durability properties can be well balanced within such ranges. Furthermore, even if continuous input is made to the touch panel with a pen, cracks, peeling, wear, etc. can be suppressed in the transparent conductive film, and further, excellent durability can be exhibited against loads caused by pen sliding and heavy pen pressure. The numerical ranges and values ​​can be selected from those described in this specification.

[0015] In the present invention, it is desirable that the sum of the transmitted image clarity of the transparent conductive film at comb widths of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm is 250% or more and less than 500%, since it is possible to provide a high-definition image. The larger the sum of the transmitted image clarity, the higher the image clarity, i.e., the higher the high definition. More preferably, the sum of the transmitted image clarity of the transparent conductive film is 300% or more. Even more preferably, the sum of the transmitted image clarity of the transparent conductive film is 400% or more. In this specification, the term "comb width" refers to the optical comb width conforming to JIS-K7105.

[0016] In the transparent conductive film of the present invention, the crystal grain size of the transparent conductive film of indium-tin composite oxide is preferably 10 to 100 nm, and the crystallinity of the transparent conductive film of indium-tin composite oxide is preferably 20 to 80%. When the crystal grain size of the transparent conductive film of indium-tin composite oxide is 10 nm or more, the transparent conductive film becomes appropriately hard due to strain around the crystal grains of the transparent conductive film, and therefore it is preferable for the transparent conductive film to have excellent pen sliding durability. More preferably, the crystal grain size of the transparent conductive film of indium-tin composite oxide is 30 nm or more. On the other hand, if the crystal grain size of the transparent conductive film of indium-tin composite oxide is 100 nm or less, the transparent conductive film is not too hard due to distortion around the crystal grains of the transparent conductive film, and therefore has excellent pen heavy pressure durability, which is preferable. More preferably, the crystal grain size of the transparent conductive film of indium-tin composite oxide is 90 nm or less. In one embodiment, the crystal grain size of the transparent conductive film of indium-tin composite oxide is 30 nm or more and 95 nm or less, for example, 40 nm or more and 90 nm or less. When the crystallinity of the transparent conductive film of indium-tin composite oxide is 20% or more, the transparent conductive film is moderately hard due to the hard crystals contained therein, and thus has excellent pen sliding durability, which is preferable. More preferably, the crystallinity of the transparent conductive film of indium-tin composite oxide is 25% or more. On the other hand, when the crystallinity of the transparent conductive film of indium-tin composite oxide is 80% or less, the transparent conductive film contains a large amount of hard crystals, but is not too hard, and therefore has excellent pen heavy pressure durability, which is preferable. In one embodiment, the crystallinity of the transparent conductive film of indium-tin composite oxide is 25% or more and 78% or less, for example, 25% or more and 76% or less.

[0017] In the transparent conductive film of the present invention, when the three-dimensional surface roughness SRa of the transparent conductive film is X, X is preferably 1 to 100 nm. If X is 1 to 100 nm, the surface protrusions of the transparent conductive film are small, so that the deformation amount of the surface protrusions is small when a pen weight pressure test is performed, and the occurrence of cracks in the transparent conductive film is suppressed, and further, since the transparent conductive film has some surface protrusions, the film winding property can be maintained, which is preferable. More preferably, X is 1 to 80 nm. Even more preferably, X is 1 to 65 nm.

[0018] The transparent conductive film in the present invention is made of an indium-tin composite oxide, and preferably contains 0.5% by mass or more and 10% by mass or less of tin oxide. Tin oxide in the indium-tin composite oxide corresponds to an impurity for indium oxide. The inclusion of tin oxide impurities increases the melting point of the indium-tin composite oxide. That is, the inclusion of impurities in tin oxide acts in the direction of inhibiting crystallization, and is an important factor that is strongly correlated with crystallinity such as crystal grain size and crystallinity. When tin oxide is contained at 0.5% by mass or more, the surface resistance of the transparent conductive film becomes a practical level, which is preferable. More preferably, the content of tin oxide is 1% by mass or more, and particularly preferably, 2% by mass or more. When the content of tin oxide is 10% by mass or less, crystallization is likely to occur in adjusting to the semi-crystalline state described below, and the pen sliding durability is good, which is preferable. The content of tin oxide is more preferably 8% by mass or less, more preferably 6% by mass or less, and particularly preferably 4% by mass or less. The surface resistance of the transparent conductive film of the present invention is preferably 50 to 900 Ω / □, and more preferably 50 to 600 Ω / □.

[0019] In the present invention, the thickness of the transparent conductive film is preferably 10 nm or more and 30 nm or less. The thickness of the transparent conductive film is an important factor that is strongly correlated with crystallinity such as crystal grain size and crystallinity. When the thickness of the transparent conductive film is 10 nm or more, the transparent conductive film does not have too much amorphous, and it is easy to give a suitable crystal grain size and crystallinity to make the semi-crystalline state described below, and as a result, it is preferable that the pen sliding durability is maintained. More preferably, the thickness of the transparent conductive film is 13 nm or more, more preferably 16 nm or more. In addition, when the thickness of the transparent conductive film is 30 nm or less, the crystal grain size of the transparent conductive film is not too large and the crystallinity is not too high, it is easy to maintain the semi-crystalline state, and it is preferable that the pen heavy pressure durability is maintained. More preferably, it is 28 nm or less, and even more preferably, it is 25 nm or less.

[0020] In the transparent conductive film of the present invention, when the three-dimensional surface roughness SRa of the surface opposite to the transparent conductive film side on the transparent plastic film substrate is Y, (X 3 +Y 3 )1 / 3 However, if the thickness is 140 nm or less, the sum of the transmitted image clarity of the transparent conductive film at comb widths of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm is 250% or more and less than 500%, which is desirable because it makes it possible to provide high-definition images. ((X 3 +Y 3 ) 1 / 3 It was confirmed that the smaller the value of (X 3 +Y 3 ) 1 / 3 More preferably, (X 3 +Y 3 ) 1 / 3 is 70 nm or less. (X 3 +Y 3 ) 1 / 3 If the thickness is 1 nm or more, the transparent conductive film has some surface protrusions, which is preferable since the film can be easily wound.

[0021] The transparent conductive film in the present invention is preferably one in which the transparent conductive film does not peel off even when an adhesion test (JIS K5600-5-6:1999) is performed on the transparent conductive film surface. A transparent conductive film in which the transparent conductive film does not peel off in an adhesion test is preferably one in which the transparent conductive film is in close contact with a layer in contact with the transparent conductive film, such as a transparent plastic substrate or a cured resin layer, and therefore cracks, peeling, wear, etc. are suppressed on the transparent conductive film even when continuous input is made to a touch panel with a pen, and further, cracks, peeling, etc. are suppressed on the transparent conductive film even when a force stronger than that expected in normal use is applied.

[0022] The transparent conductive film of the present invention preferably has a mandrel diameter of less than 20 mm at which cracks or peeling occurs when the bent portion of the transparent conductive film is observed with a 10x magnifying glass in a bending resistance test (JIS K5600-5-1:1999) on the transparent conductive film side. If the mandrel diameter is less than 20 mm, the layer in contact with the transparent conductive film does not break when a pen pressure test is performed, and cracks do not occur in the transparent conductive film, which is preferable. The mandrel diameter is more preferably 18 mm or less. In one embodiment, the value in the flex test may be 1 mm or more, for example, 8 mm or more, 10 mm or more, and in one embodiment, the value in the flex test may be 13 mm or more, for example, 15 mm or more. It is preferable that the thickness is within such a range because the layer in contact with the transparent conductive film does not break when a pen weight pressure test is performed, and cracks do not occur in the transparent conductive film. It is also possible to provide a transparent conductive film that has both excellent pen sliding durability and excellent pen heavy pressure durability.

[0023] In the transparent conductive film of the present invention, the thickness of the transparent plastic film substrate is preferably in the range of 100 to 250 μm, more preferably 130 to 220 μm. When the plastic film has a thickness of 100 μm or more, mechanical strength is maintained, deformation due to pen input is small, and durability against pen sliding and durability against pen heavy pressure is excellent, which is preferable. On the other hand, when the film is used in a touch panel, the load for positioning by pen input is not particularly large, which is preferable.

[0024] The transparent conductive film in the present invention preferably has a curable resin layer between the transparent conductive film and the plastic film substrate. The presence of the curable resin layer increases the adhesion of the transparent conductive film and disperses the force applied to the transparent conductive film, so that cracks, peeling, wear, etc. of the transparent conductive film are suppressed in a pen sliding test, and furthermore, cracks, peeling, etc. of the transparent conductive film are suppressed in a pen heavy pressure test, which is preferable.

[0025] The crystallinity of the transparent conductive film in the present invention is neither too high nor too low (such crystallinity is called semi-crystalline or semi-crystalline). It is very difficult to make a transparent conductive film stable and semi-crystalline. This is because the state where the phase change from amorphous to crystalline is stopped in the middle is semi-crystalline. Therefore, the film is sensitive to the amount of moisture in the film-forming atmosphere, which is a parameter related to crystallinity, and is particularly sensitive to hydrogen atom-containing gas. If the amount of hydrogen atom-containing gas or moisture in the film-forming atmosphere is even slightly small, the film will be almost completely crystalline (high crystallinity), and conversely, if the amount of hydrogen atom-containing gas or moisture in the film-forming atmosphere is even slightly large, the film will be amorphous (low crystallinity).

[0026] The manufacturing method for obtaining the transparent conductive film of the present invention is not particularly limited, but for example, the following manufacturing method can be preferably exemplified. A sputtering method is preferably used as a method for forming a transparent conductive film of crystalline indium-tin composite oxide on at least one surface of a transparent plastic film substrate. In order to manufacture a transparent conductive film with high productivity, it is preferable to use a so-called roll-type sputtering device that supplies a film roll, and after film formation, winds up the film roll. A hydrogen atom-containing gas (hydrogen, ammonia, hydrogen + argon mixed gas, etc., as long as it contains hydrogen atoms, but water is excluded) is introduced into the film formation atmosphere by a mass flow controller in the amount described below, and further, the film temperature during sputtering is set to 0°C or less, and a sintered target of indium-tin composite oxide containing 0.5 to 10 mass% tin oxide is used, and the thickness of the transparent conductive film of indium-tin composite oxide is adjusted to 10 to 30 nm, and a transparent conductive film of indium-tin composite oxide having a three-dimensional surface roughness SRa of 1 to 100 nm is preferably formed on a transparent plastic film. In the film formation atmosphere during sputtering, a hydrogen atom-containing gas has the effect of inhibiting crystallization of the transparent conductive film. When hydrogen gas is flowed in the film formation atmosphere, the value of (hydrogen gas flow rate)÷(inert gas flow rate+hydrogen gas flow rate)×100 (sometimes simply referred to as hydrogen concentration) is preferably 0.01 to 3.00%. The hydrogen concentration may be, for example, 0.01% to 2.00%, or 0.01% to 1.00%. Having the hydrogen concentration within such a range can contribute to obtaining good results in both the ON resistance value in a pen sliding durability test and in a pen heavy pressure durability test, for example. Examples of inert gases include helium, neon, argon, krypton, and xenon. When a hydrogen-atom-containing gas other than hydrogen gas is used, the amount of hydrogen gas (= hydrogen molecules) can be calculated by converting the amount of hydrogen atoms contained in the hydrogen-atom-containing gas into the amount of hydrogen gas. When the hydrogen-atom-containing gas is precisely flowed in the film-forming atmosphere by a mass flow controller, the gas outlet is arranged so that the hydrogen-atom-containing gas can be uniformly sprayed in the direction perpendicular to the longitudinal direction of the film roll. This makes it difficult for the transparent conductive film to have a mixture of high and low crystallinity parts, and makes it easy to obtain a uniform semi-crystalline transparent conductive film, so that it is possible to suitably obtain a transparent conductive film having both excellent pen sliding durability and pen heavy pressure durability. It is known that the crystallinity of the transparent conductive film decreases when there is a lot of water in the film-forming atmosphere, so the amount of water in the film-forming atmosphere is also an important factor. When a hydrogen-atom-containing gas is used, the median value (the intermediate value between the maximum value and the minimum value) of the ratio of water pressure to the inert gas in the film-forming atmosphere during sputtering on the film roll is 1.0×10 -4 ~2.0×10 -3 Furthermore, the difference between the maximum and minimum values ​​of the ratio of water pressure to inert gas pressure in the deposition atmosphere during sputtering from the start to the end of deposition was 1.0×10 -3If the thickness is less than 100 nm, the crystallinity of the transparent conductive film is uniform over the entire length of the film, and if the amount of water released from the film during the formation of the transparent conductive film is reduced and a uniform amount of water is released over the entire length of the film, this is preferable, since it eliminates the need for precise control of the amount of water. However, the median value of the ratio of water pressure to the inert gas also depends somewhat on the content of tin oxide in the transparent conductive film of indium-tin composite oxide and the thickness of the transparent conductive film. When the amount of tin oxide added in the transparent conductive film of indium-tin composite oxide is large or the transparent conductive film is thin, it is desirable to set the median value of the ratio of water pressure to the inert gas to a lower value within the above range. Conversely, when the content of tin oxide in the transparent conductive film of indium-tin composite oxide is small or the transparent conductive film is thick, it is desirable to set the median value of the ratio of water pressure to the inert gas to a higher value within the above range. It is preferable to form a transparent conductive film on a transparent plastic film by setting the film temperature at 0°C or less during sputtering. The film temperature during film formation is substituted by the set temperature of a temperature controller that adjusts the temperature of the center roll that the traveling film contacts. Here, FIG. 5 shows a schematic diagram of an example of a sputtering device that is preferably used in the present invention, in which a traveling film 1 partially contacts the surface of a center roll 2 and travels. An indium-tin sputtering target 4 is installed via a chimney 3, and a thin film of indium-tin composite oxide is deposited and laminated on the surface of the film 1 traveling on the center roll 2. The temperature of the center roll 2 is controlled by a temperature controller (not shown). If the film temperature is 0°C or less, it is possible to suppress the release of impurity gases such as water and organic gases from the film that cause the crystallinity of the transparent conductive film to vary, so that it is preferable that the crystallinity of the transparent conductive film is easily uniform from the start of film formation to the end of film formation. When a hydrogen atom-containing gas is used, the median value (the intermediate value between the maximum value and the minimum value) of the ratio of water pressure to inert gas in the film formation atmosphere during sputtering is 1.0×10 -4 ~2.0×10 -3It is preferable that the ratio of water pressure to inert gas in the film formation atmosphere during sputtering is within the above range, since the hydrogen atom-containing gas effectively inhibits the crystallinity of the transparent conductive film. It is also preferable to add oxygen gas during sputtering in order to bring the surface resistance and total light transmittance of the transparent conductive film to a practical level. The main focus of this manufacturing method is to eliminate as much as possible the influence of crystallinity due to water, which is a factor that causes the crystallinity of the transparent conductive film to vary, and to control the crystallinity by using a hydrogen-containing gas.

[0027] To control the moisture content when forming an indium-tin oxide film on a plastic film, it is preferable to actually observe the moisture content during film formation rather than observing the ultimate vacuum for the following two reasons.

[0028] The first reason is that when a film is formed on a plastic film by sputtering, the film is heated and moisture is released from the film, increasing the amount of moisture in the film-forming atmosphere and exceeding the amount of moisture measured when the ultimate vacuum is measured; therefore, it is more accurate to express this in terms of the amount of moisture at the time of film formation rather than in terms of the ultimate vacuum.

[0029] The second reason is the case of a device that inputs a large amount of transparent plastic film. In such a device, the film is input in the form of a film roll. When the film is rolled and input into a vacuum chamber, the outer layer of the roll is easy to remove water, but the inner layer of the roll is difficult to remove water. When the ultimate vacuum is measured, the film roll is stopped, but during film formation, the film roll runs, and the inner layer of the film roll, which contains a lot of water, is unwound, so the amount of moisture in the film formation atmosphere increases and is greater than the amount of moisture when the ultimate vacuum is measured. In the present invention, the amount of moisture in the film formation atmosphere can be controlled by observing the ratio of the moisture pressure to the inert gas in the film formation atmosphere during sputtering.

[0030] It is preferable to pass the film through a bombardment process before forming the transparent conductive film. The bombardment process is a process in which a voltage is applied to discharge and generate plasma while only an inert gas such as argon gas or a mixture of a reactive gas such as oxygen and an inert gas is flowing. Specifically, it is preferable to bombard the film by RF sputtering using a SUS target or the like. The bombardment process exposes the film to plasma, which releases water and organic components from the film, and the amount of water and organic components released from the film when forming the transparent conductive film is reduced, which is preferable because it makes it easier to uniformize the crystallinity of the transparent conductive film from the start to the end of film formation. In addition, the bombardment process activates the layer that the transparent conductive film comes into contact with, which improves the adhesion of the transparent conductive film, which is preferable because it improves the pen sliding durability and pen heavy pressure durability.

[0031] In the film roll for forming the transparent conductive film, the height difference between the most convex and most concave points on the roll end face is preferably 10 mm or less. If it is 10 mm or less, there will be less unevenness in the way water and organic components are released from the film end face when the film roll is inserted into a sputtering device, which is preferable because it makes it easier to uniformize the crystallinity of the transparent conductive film from the start to the end of film formation.

[0032] In the method for forming a transparent conductive film of crystalline indium-tin composite oxide on at least one surface of a transparent plastic film substrate, it is preferable to introduce oxygen gas during sputtering. When oxygen gas is introduced during sputtering, there is no problem due to oxygen deficiency in the transparent conductive film of indium-tin composite oxide, and the surface resistance of the transparent conductive film is low and the total light transmittance is high, which is preferable. Therefore, in order to make the surface resistance and total light transmittance of the transparent conductive film practical levels, it is preferable to introduce oxygen gas during sputtering. The total light transmittance of the transparent conductive film of the present invention is preferably 70 to 95%.

[0033] The transparent conductive film of the present invention is preferably obtained by forming a transparent conductive film of indium-tin composite oxide on a transparent plastic film substrate and then performing a heat treatment at 80 to 200°C for 0.1 to 12 hours in an oxygen-containing atmosphere after the transparent conductive film is laminated. If the temperature is 80°C or higher, it is easy to slightly increase the crystallinity to make the film semi-crystalline, and the pen sliding durability is improved, which is preferable. If the temperature is 200°C or lower, the flatness of the transparent plastic film is ensured, which is preferable.

[0034] <Transparent plastic film substrate> The transparent plastic film substrate used in the present invention is a film obtained by melt-extruding or solution-extruding an organic polymer into a film shape, and then stretching, cooling, and heat-setting the film in the longitudinal and / or transverse directions as necessary. Examples of the organic polymer include polyethylene, polypropylene, polyethylene terephthalate, polyethylene-2,6-naphthalate, polypropylene terephthalate, polybutylene terephthalate, nylon 6, nylon 4, nylon 66, nylon 12, polyimide, polyamideimide, polyethersulfane, polyetheretherketone, polycarbonate, polyarylate, cellulose propionate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyetherimide, polyphenylene sulfide, polyphenylene oxide, polystyrene, syndiotactic polystyrene, and norbornene-based polymers.

[0035] Among these organic polymers, preferred are polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, syndiotactic polystyrene, norbornene-based polymers, polycarbonate, polyarylate, etc. Furthermore, these organic polymers may be copolymerized with small amounts of monomers of other organic polymers or blended with other organic polymers.

[0036] The transparent plastic film substrate used in the present invention may be subjected to a surface activation treatment such as corona discharge treatment, glow discharge treatment, flame treatment, ultraviolet irradiation treatment, electron beam irradiation treatment, or ozone treatment, as long as the object of the present invention is not impaired.

[0037] When a curable resin layer is applied to a transparent plastic film substrate, the transparent conductive film adheres strongly to the curable resin layer and the force applied to the transparent conductive film can be dispersed, so that cracks, peeling, wear, etc. are suppressed in the transparent conductive film in the pen sliding test, and furthermore, cracks, peeling, etc. are suppressed in the transparent conductive film in the pen weight pressure test, which is preferable. In addition, when a transparent conductive film is formed on the surface of a curable resin layer with irregularities, the true contact area when the transparent conductive thin film contacts the glass during the pen sliding test is reduced, so that the slipperiness between the glass surface and the transparent conductive film is improved, and the pen sliding durability is improved, and the winding property of the film roll and the anti-Newton ring property can be expected, but if the irregularities are too large, the deformation amount of the surface protrusions during the pen weight pressure test becomes large, and cracks occur in the transparent conductive film, which is not preferable. Therefore, when the three-dimensional surface roughness SRa of the transparent conductive film is X, it is preferable that X is 1 to 100 nm as the surface irregularities. In addition, the curable resin layer may be applied to both sides of the transparent plastic film substrate. When the three-dimensional surface roughness SRa of the curable resin layer on the side opposite to the side on which the transparent conductive film is formed is Y, Y is preferably 1 to 139 nm. Details of the curable resin layer are described below.

[0038] The curable resin preferably used in the present invention is not particularly limited as long as it is a resin that is cured by application of energy such as heating, ultraviolet irradiation, electron beam irradiation, etc., and examples of the resin include silicone resin, acrylic resin, methacrylic resin, epoxy resin, melamine resin, polyester resin, urethane resin, etc. From the viewpoint of productivity, it is preferable to use an ultraviolet curable resin as the main component.

[0039] Examples of such ultraviolet-curable resins include polyfunctional acrylate resins such as acrylic acid or methacrylic acid esters of polyhydric alcohols, and polyfunctional urethane acrylate resins synthesized from diisocyanates, polyhydric alcohols, and hydroxyalkyl esters of acrylic acid or methacrylic acid, etc. If necessary, these polyfunctional resins can be copolymerized by adding monofunctional monomers such as vinylpyrrolidone, methyl methacrylate, and styrene.

[0040] In order to improve the adhesion between the transparent conductive thin film and the curable resin layer, it is effective to treat the surface of the curable resin layer by the following method. Specific methods include a discharge treatment method in which glow or corona discharge is irradiated to increase carbonyl groups, carboxyl groups, and hydroxyl groups, and a chemical treatment method in which acid or alkali is treated to increase polar groups such as amino groups, hydroxyl groups, and carbonyl groups.

[0041] The ultraviolet curing resin is usually used by adding a photopolymerization initiator. As the photopolymerization initiator, any known compound that absorbs ultraviolet light and generates radicals can be used without any particular limitation, and examples of such photopolymerization initiators include various benzoins, phenyl ketones, benzophenones, etc. The amount of the photopolymerization initiator added is usually 1 to 5 parts by mass per 100 parts by mass of the ultraviolet curing resin.

[0042] In the present invention, the curable resin layer preferably contains inorganic particles or organic particles in addition to the curable resin, which is the main component. By dispersing inorganic particles or organic particles in the curable resin, it is possible to form irregularities on the surface of the curable resin and improve the surface roughness over a wide area.

[0043] Examples of the inorganic particles include silica, etc. Examples of the organic particles include polyester resin, polyolefin resin, polystyrene resin, polyamide resin, etc.

[0044] In addition to inorganic particles and organic particles, it is also preferable to use a resin incompatible with the curable resin in addition to the curable resin, which is the main component. By using a small amount of a resin incompatible with the curable resin of the matrix, phase separation occurs in the curable resin, and the incompatible resin can be dispersed in the form of particles. The dispersed particles of the incompatible resin can form unevenness on the surface of the curable resin, improving the surface roughness over a wide area.

[0045] Examples of the incompatible resin include polyester resin, polyolefin resin, polystyrene resin, polyamide resin, and the like.

[0046] Here, as an example, the blending ratio of inorganic particles in the curable resin layer directly below the transparent conductive film is shown. The inorganic particles are preferably 0.1 to 20 parts by mass, more preferably 0.1 to 15 parts by mass, and particularly preferably 0.1 to 12 parts by mass per 100 parts by mass of the ultraviolet curable resin. When the blending amount of the inorganic particles is 0.1 to 20 parts by mass per 100 parts by mass of the ultraviolet-curable resin, the convex parts formed on the surface of the curable resin layer are not too small, and three-dimensional surface roughness can be effectively imparted; when a pen-loaded pressure test is performed, the deformation amount of the surface protrusions is small, and the occurrence of cracks in the transparent conductive film is suppressed, making it possible to provide high-definition images; and further, since the transparent conductive film has some surface protrusions, the film winding properties can be maintained, which is preferable.

[0047] As an example, the blending ratio of inorganic particles in the curable resin layer on the opposite side to the side on which the transparent conductive film is formed is shown below. The inorganic particles are preferably 0.1 to 25 parts by mass, more preferably 0.1 to 15 parts by mass, and particularly preferably 0.1 to 12 parts by mass per 100 parts by mass of the ultraviolet curable resin. When the blending amount of the inorganic particles is 0.1 to 25 parts by mass per 100 parts by mass of the ultraviolet-curable resin, the convex portions formed on the surface of the curable resin layer are not too small, and three-dimensional surface roughness can be effectively imparted, making it possible to provide high-definition images, and further since the transparent conductive film has some surface protrusions, the film winding properties can be maintained, which is preferable.

[0048] The above-mentioned ultraviolet curable resin, photopolymerization initiator, and resin incompatible with inorganic particles, organic particles, and ultraviolet curable resin are dissolved in a common solvent to prepare a coating liquid. There is no particular limitation on the solvent used, and for example, alcohol-based solvents such as ethyl alcohol, isopropyl alcohol, etc., ester-based solvents such as ethyl acetate, butyl acetate, etc., ether-based solvents such as dibutyl ether, ethylene glycol monoethyl ether, etc., ketone-based solvents such as methyl isobutyl ketone, cyclohexanone, etc., aromatic hydrocarbon-based solvents such as toluene, xylene, solvent naphtha, etc., can be used alone or in combination.

[0049] The concentration of the resin component in the coating liquid can be appropriately selected in consideration of the viscosity according to the coating method. For example, the total amount of the ultraviolet curing resin, the photopolymerization initiator, and the high molecular weight polyester resin in the coating liquid is usually 20 to 80 mass %. In addition, other known additives, such as a silicone-based leveling agent, may be added to the coating liquid as necessary.

[0050] In the present invention, the prepared coating solution is coated onto a transparent plastic film substrate. The coating method is not particularly limited, and any conventionally known method such as bar coating, gravure coating, or reverse coating can be used.

[0051] The solvent in the coated coating liquid is evaporated and removed in the next drying process. In this process, the high molecular weight polyester resin that was uniformly dissolved in the coating liquid becomes particles and precipitates in the UV-curable resin. After the coating is dried, the plastic film is irradiated with UV rays, causing the UV-curable resin to crosslink and harden, forming a hardened resin layer. In this hardening process, the particles of the high molecular weight polyester resin are fixed in the hard coat layer, and protrusions are formed on the surface of the hardened resin layer, improving surface roughness over a wide area.

[0052] The thickness of the curable resin layer is preferably in the range of 0.1 to 15 μm, more preferably in the range of 0.5 to 10 μm, and particularly preferably in the range of 1 to 8 μm. When the thickness of the curable resin layer is 0.1 μm or more, sufficient protrusions are formed, which is preferable. On the other hand, when the thickness is 15 μm or less, productivity is good, which is preferable. EXAMPLES

[0053] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Various measurements and evaluations in the examples were performed according to the following methods. (1) Total light transmittance The total light transmittance was measured using NDH-2000 manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with JIS-K7136-1:1997.

[0054] (2) Surface resistance The measurement was performed by the four-terminal method in accordance with JIS-K7194:1994. The measurement device used was Lotesta AX MCP-T370 manufactured by Mitsubishi Chemical Analytech Co., Ltd.

[0055] (3) Three-dimensional center surface average surface roughness SRa The three-dimensional central plane average surface roughness SRa is specified in ISO 25178, and was determined using a three-dimensional surface profiler Bertscan (R5500H-M100 (measurement conditions: wave mode, measurement wavelength 560 nm, objective lens 10x) manufactured by Ryoka Systems Co., Ltd.). Five measurements were taken, and the average value was determined. Here, the values ​​were rounded off to the first decimal place in nm units. Here, the three-dimensional surface roughness SRa of the transparent conductive film is designated as X, and the three-dimensional surface roughness SRa of the surface opposite the transparent conductive film on the transparent plastic film substrate is designated as Y.

[0056] (4) Crystal grain size A film sample with a transparent conductive thin film layer laminated thereon was cut into pieces measuring 1 mm x 10 mm, and attached to the top surface of a suitable resin block with the conductive thin film surface facing outward. After trimming, ultrathin sections roughly parallel to the film surface were prepared using a general ultramicrotome technique. The slice was observed under a transmission electron microscope (JEOL, JEM-2010) to select a surface area of ​​the conductive thin film that was not significantly damaged, and photographed at an accelerating voltage of 200 kV and a direct magnification of 40,000 times. In the crystal grains observed under a transmission electron microscope, the longest part of each crystal grain is measured, and the average value of these measurements is taken as the crystal grain size. Here, Figures 1 to 4 show an example of how to determine the longest part when measuring the longest part of the crystal grain. That is, the longest part is determined by the length of the straight line that can measure the largest grain size of each crystal grain.

[0057] (5) Thickness of the transparent conductive film (film thickness) A film sample piece laminated with a transparent conductive thin film layer was cut into pieces measuring 1 mm x 10 mm and embedded in epoxy resin for electron microscopes. This was fixed to a sample holder of an ultramicrotome, and a thin cross-sectional slice parallel to the short side of the embedded sample piece was prepared. Next, a transmission electron microscope (JEOL, JEM-2010) was used to photograph a portion of the thin film of the slice that was not significantly damaged, at an accelerating voltage of 200 kV and a magnification of 10,000 times in bright field, and the film thickness was determined from the photograph obtained.

[0058] (6) Pen sliding durability test The transparent conductive film according to the present invention was used as one panel plate, and a transparent conductive thin film made of an indium-tin composite oxide thin film (tin oxide content: 10% by mass) having a thickness of 20 nm was used as the other panel plate by sputtering on a glass substrate. The two panels were arranged with epoxy beads having a diameter of 30 μm interposed between them so that the transparent conductive thin films faced each other, to prepare a touch panel. Next, a load of 5.0 N was applied to a polyacetal pen (tip shape: 0.8 mmR), and a linear sliding test of 180,000 round trips was performed on the touch panel. In this test, the load of the pen was applied to the transparent conductive film surface according to the present invention. The sliding distance at this time was 30 mm, and the sliding speed was 180 mm / sec. After this sliding durability test, the ON resistance (resistance value when the movable electrode (film electrode) and the fixed electrode contacted each other) was measured when the sliding part was pressed with a pen load of 0.8 N. It is desirable that the ON resistance is 10 kΩ or less. In the comparative examples, the films in the respective comparative examples were used in place of the transparent conductive film according to the present invention.

[0059] (7) Pen weight test The transparent conductive film according to the present invention was cut to 50 mm x 50 mm and used as one panel plate, and a transparent conductive thin film made of an indium-tin composite oxide thin film (tin oxide content: 10 mass%) having a thickness of 20 nm was used as the other panel plate by sputtering on a glass substrate. The two panel plates were arranged with epoxy beads having a diameter of 30 μm interposed between them so that the transparent conductive thin films faced each other, and the panel plate on the film side and the panel plate on the glass side were attached with double-sided tape adjusted to a thickness of 120 μm to produce a touch panel. A load of 35 N was applied with a polyacetal pen (tip shape 0.8 mmR) at a position 2.0 mm from the end of the double-sided tape, and linear sliding was performed 10 times (reciprocating 5 times) parallel to the double-sided tape. In this test, the load of the pen was applied to the transparent conductive film surface according to the present invention. The sliding distance at this time was 30 mm, and the sliding speed was 20 mm / sec. However, the sliding was performed at a position where there were no epoxy beads. After sliding, the transparent conductive film is removed and the surface resistance (four-terminal method) is measured at any five points on the sliding area, and the average value is calculated. When measuring the surface resistance, four terminals are arranged in a direction perpendicular to the sliding area, with the sliding area between the second and third terminals. The average surface resistance value of the sliding area is divided by the surface resistance value of the unslided area (measured using the four-terminal method) to calculate the rate of increase in surface resistance value. In the comparative examples, the films in the respective comparative examples were used in place of the transparent conductive film according to the present invention.

[0060] (8) Measurement of the tin oxide content in transparent conductive films Cut the sample (approximately 15 cm 2 ) into a quartz Erlenmeyer flask, 20 ml of 6 mol / l hydrochloric acid was added, and the flask was sealed with film to prevent the acid from volatilizing. The flask was left at room temperature for 9 days with occasional shaking to dissolve the transparent conductive film. The remaining film was removed, and the hydrochloric acid in which the transparent conductive film had dissolved was used as the measurement solution. The In and Sn in the solution were determined by the calibration curve method using an ICP emission spectrometer (manufacturer: Rigaku, model: CIROS-120 EOP). The measurement wavelength for each element was selected to be one with no interference and high sensitivity. The standard solutions were also prepared by diluting commercially available standard solutions of In and Sn.

[0061] (9) Adhesion test The test was carried out in accordance with JIS K5600-5-6:1999.

[0062] (10) Bending resistance test The test was conducted in accordance with JIS K5600-5-1: 1999. However, if no cracking or peeling occurred up to a mandrel diameter of 13 mm, no further bending resistance tests were conducted, and all were recorded as 13 mm.

[0063] (11) Transmitted image clarity test In accordance with JIS-K7105, the transmitted image clarity of the transparent conductive film was measured at comb widths of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm, and the sum of the transmitted image clarity for each comb width was calculated. The measurement device used was an image clarity measuring device ICM-1T manufactured by Suga Test Instruments Co., Ltd.

[0064] The transparent plastic film substrate used in the examples and comparative examples is a biaxially oriented transparent PET film (A4340, manufactured by Toyobo Co., Ltd., thickness is shown in Table 1) having an easy-adhesion layer on both sides. As a curable resin layer, silica particles (Snowtex ZL, manufactured by Nissan Chemical Industries Co., Ltd.) were mixed with 100 parts by mass of a photopolymerization initiator-containing acrylic resin (Seikabeam (registered trademark) EXF-01J, manufactured by Dainichi Seika Chemical Industries Co., Ltd.) in an amount shown in Table 1, and a mixed solvent of toluene / MEK (8 / 2: mass ratio) was added as a solvent so that the solid content concentration was 50% by mass, and the mixture was stirred and dissolved uniformly to prepare a coating liquid (hereinafter, this coating liquid is referred to as coating liquid A). The prepared coating liquid was applied using a Mayer bar so that the coating film had a thickness of 5 μm. After drying at 80 ° C. for 1 minute, ultraviolet light was irradiated (light amount: 300 mJ / cm 2 ) using an ultraviolet light irradiation device (UB042-5AM-W, manufactured by Eye Graphics Co., Ltd.). 2 The curable resin layers were provided on both sides of the transparent plastic substrate.

[0065] (Examples 1 to 8) Each example was carried out under the conditions shown in Table 1 as follows. Put the film into the vacuum chamber and measure 1.5×10 -4 Then, oxygen was introduced, followed by introduction of argon as an inert gas and hydrogen gas as a hydrogen-containing gas at the concentrations shown in Table 1, until the total pressure reached 0.6 Pa. 3W / cm for an indium-tin oxide composite sintered target or an indium oxide sintered target that does not contain tin oxide 2 A transparent conductive film was formed by DC magnetron sputtering. The film thickness was controlled by changing the speed at which the film passed over the target. The ratio of water pressure to inert gas in the film formation atmosphere during sputtering was measured using a gas analyzer (Transpector XPR3, manufactured by Inficon). In each example level, in order to adjust the ratio of water pressure to inert gas in the film formation atmosphere during sputtering, the presence or absence of a bombardment process, the unevenness height difference on the end surface of the film roll, and the temperature of the heating medium of the temperature regulator that controls the temperature of the center roll in contact with the film were adjusted as shown in Table 1. The temperature that is exactly in the middle between the maximum and minimum temperatures from the start of film formation on the film roll to the end of film formation is listed in Table 1 as the center value. The film on which the transparent conductive film was formed and laminated was subjected to the heat treatment shown in Table 1, and then the measurement was carried out. The measurement results are shown in Table 1.

[0066] (Comparative Examples 1 to 9) A transparent conductive film was prepared and evaluated in the same manner as in Example 1 under the conditions shown in Table 1. However, in Comparative Example 7, no curable resin layer was provided. However, in Comparative Example 8, the thickness of the coating of the curable resin layer was adjusted to 20 μm. The results are shown in Table 2.

[0067] [Table 1A]

[0068] [Table 1B]

[0069] [Table 2A]

[0070] [Table 2B]

[0071] As shown in Tables 1A and 1B, the transparent conductive films of Examples 1 to 8 are excellent in pen sliding durability, pen heavy pressure durability, and high definition, and combine all the characteristics. However, as shown in Table 2, Comparative Examples 1 to 9 do not satisfy all of the pen sliding durability, pen heavy pressure durability, and high definition. [Industrial Applicability]

[0072] As described above, according to the present invention, a transparent conductive film excellent in pen sliding durability, pen heavy pressure durability and high definition can be produced, which is extremely useful for applications such as resistive film touch panels. [Explanation of symbols]

[0073] 1. Film 2. Center roll 3. Chimney 4. Indium-tin oxide target

Claims

1. the crystal grain size of the transparent conductive film of indium-tin composite oxide is 10 to 100 nm, the degree of crystallinity of the transparent conductive film of indium-tin composite oxide is 20 to 80%, the transparent conductive film of indium-tin composite oxide contains 0.5 to 10 mass % of tin oxide, the thickness of the transparent conductive film of indium-tin composite oxide is 10 to 30 nm, and when the three-dimensional surface roughness SRa of the transparent conductive film of indium-tin composite oxide is X, X is 1 to 100 nm, and further when the three-dimensional surface roughness SRa of the surface of the transparent plastic film substrate opposite to the transparent conductive film side is Y, (X 3 +Y 3 ) 1 / 3 A transparent conductive film having a thickness of 140 nm or less.

2. 2. The transparent conductive film according to claim 1, wherein the transparent conductive film does not peel off when an adhesion test (JIS K5600-5-6:1999) is conducted on the surface of the transparent conductive film, and a bending resistance test (JIS K5600-5-1:1999) is conducted on the transparent conductive film side of the indium-tin composite oxide of the transparent conductive film, and when the bending portion is observed with a 10x magnifying glass, the mandrel diameter at which cracks or peeling occurs is smaller than 20 mm.

3. 3. The transparent conductive film according to claim 1, wherein the thickness of the transparent conductive film is 100 to 250 μm.

4. 4. The transparent conductive film according to claim 1, further comprising a curable resin layer between the transparent conductive film of indium-tin composite oxide and a transparent plastic film substrate.

Citation Information

Patent Citations

  • Transparent conductive layered product

    JP1996064034A

  • Transparent electrically conductive film, transparent electrically conductive sheet and touch panel

    JP2002163933A

  • Transparent conductive film

    JP2010080290A

  • Transparent conductive film and resistance film-type touch panel

    JP2014225405A

  • Transparent conductive laminate

    JP2016212789A